OPTIMALISASI PEMENUHAN HAK DAN PERLINDUNGAN PEREMPUAN DAN ANAK MELALUI PEMBENTUKAN PERATURAN DAERAH - Ni Gusti Agung Ayu Mas Tri Wulandari; I Gusti Ayu Eviani Yuliantari (LPSDI Bina Patria, 2024)
around violence against women and children always attracts attention. Violence experienced by women and children can be seen in incidents related to violence, exploitation and even trafficking in women and children. Anticipating this, their legal protection must be a priority scale for the Political Elite in Bangli Regency, especially from the legislature, so that they have a legal umbrella, in a Regional Regulation, to fight for their rights if violations occur. The research method used is normative juridical or library research related to normative legal substance, to find the truth based on scientific logic viewed from the normative side by examining library materials or secondary data consisting of primary legal materials and secondary legal materials. The results of this research show that optimizing the fulfillment of the rights and protection of women and children in Bangli Regency must meet several indicators. The drafting of the Bangli Regency Regional Regulation on the Protection of Women and Children has had a social impact on families, communities and the business world. This impact is the optimization of the role of the family, community and business world in fulfilling the rights and protection of women and children in Bangli Regency.